Reducing the risk of patient suicide in Tuscany. (November 2020) - Dagliana, Giulia; Albolino, Sara; Belloni, Laura; Bellandi, Tommaso
Abstract : Patient suicide is one of the most frequent incidents in healthcare facilities to be reported to the National Observatory of Sentinel Events in Italy. Despite national initiatives, in Tuscany potentially preventable patient suicides still occur in both acute and community care settings. We describe here an aggregated qualitative analysis of 14 patient suicides that took place in public health services between 2017 and 2018. We outline the methodology and results of an improvement action we enacted in the healthcare system that involved reviewing and reinforcing relevant managerial strategies and clinical activities, with the aim of reducing potentially preventable patient suicides.